A Facile Hydrothermal Synthesis of Ceo2-Co3o4 Composites: Versatile Catalysts for Oxygen Evolution, Methanol Oxidation, Urea Oxidation, and Catalytic Dye Reduction - Casagrande-Denardin, J (ELSEVIER, 2025)
Designing effective, low-cost catalysts is essential for applications that address both energy and environmental challenges. In this study, CeO2-Co3O4 composites are synthesized via a facile hydrothermal method using varying CeO2 concentrations, and the resulting materials are labeled as CeCo-1 and CeCo-2. These cost-effective composites function as catalysts for rhodamine B dye reduction and as electrocatalysts for the oxygen evolution reaction (OER), methanol oxidation reaction (MOR), and urea oxidation reaction (UOR). The synthesized samples were characterized using multiple techniques. X-ray diffraction (XRD) confirmed the presence of both CeO2 and Co3O4 phases in the composites. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and high-resolution TEM (HR-TEM) verified the attachment of Co3O4 nanosphericals onto CeO2 nanorods. Energy-dispersive X-ray analysis (EDX) and elemental mapping confirm the presence of Ce, Co, and O in the composite structure. The synthesized materials are employed as catalysts for the reduction of rhodamine B dye. Among them, CeCo-2 demonstrates superior catalytic activity, achieving a pseudo-first-order rate constant of 0.407 min-1 and 94% dye reduction within 7 min. These materials were also evaluated as electrocatalysts for OER, MOR, and UOR. CeCo-2 exhibits higher electrochemically active surface area values for all three reactions. Additionally, all electrocatalysts show excellent durability in the 1.0 M KOH solution during OER, MOR, and UOR testing. This study presents a cost-effective method for synthesizing catalysts intended for energy and environmental applications.